WHOLE BODY COMPUTED TOMOGRAPHIC CHARACTERISTICS OF SKELETAL AND CARDIAC MUSCULAR METASTATIC NEOPLASIA IN DOGS AND CATS. Issue 3 (27th February 2013) - Vignoli, Massimo; Terragni, Rossella; Rossi, Federica; Frühauf, Lukas; Bacci, Barbara; Ressel, Lorenzo; Capitani, Ombretta; Marconato, Laura
<x xml:space="preserve">Abstract</x> Muscular metastatic neoplasia has been reported to be rare in domestic animals, however previous studies were based primarily on necropsy findings. The purpose of this retrospective study was to describe whole body computed tomography (CT) characteristics of confirmed muscular metastases in a cohort of dogs and cats presented for oncology evaluation. Medical records of 1201 oncology patients were reviewed. Included animals underwent pre and postcontrast whole body CT, and CT‐guided tru‐cut biopsy or fine needle aspiration of one or more metastatic lesions. Twenty‐one dogs and six cats met inclusion criteria, representing 2.08% of all canine oncology patients and 3.1% of all feline oncology patients. Mean age was 9.6 years. Postcontrast CT characteristics included well‐demarcated, oval‐to‐round lesions with varying enhancement patterns: ring enhancing (n = 16), heterogeneously enhancing (n = 8), or homogeneously enhancing (n = 5). Five animals showed concurrent and varying nodular patterns. In seven cases (five dogs and two cats), one single muscular nodule was observed. In 20 cases, two or more lesions were observed. In two cases, cardiac hypodense nodules were observed in the postcontrast CT, while appearing isodense in the precontrast study. Necropsy confirmed neoplasia in both of them. Locations of muscular metastases included epaxial/paraspinal muscles of the cervical, thoracic, and lumbar spine (n = 18), superficial muscles of the thoracic wall (n = 13), scapular/shoulder region (n = 3), hind limb (n = 3), and abdominal wall muscles (n = 1). Findings supported the use of pre and postcontrast whole body CT for oncologic staging in dogs and cats, especially for primary tumors characterized by a high metastatic rate.